A vigência do medo, sofrimento e sobrecarga física para o trabalhador no corte da cana de açúcar no estado de São Paulo - Iracimara Anchieta Messias; Robinzon Piñeros Lizarazo (Confins)
This article presents how fear, suffering and physical attrition determine the work of manual sugarcane cutting for the production of ethanol biofuel. The study was conducted in the western region of the state of São Paulo, at two different times: - in the first one, the results are presented when the activity of manual cutting represented 70% of the production in the region. In a second moment, the results are discussed with other studies carried out in recent years, with mechanization accounting for 90% of the cut in the state of São Paulo. The study was conducted with a focus on the ergonomics of the activity, using the psychodynamic approach to work, with questions related to the pleasure and suffering of these workers. Systematic observation of the work was performed using the Ergonomic Analysis of the Work and the Win-Owas postural analysis instrument was applied, for knowledge of physical wear. From the results obtained, questions related to suffering and fear emerge, within some topics such as work by production, physical exhaustion and distrust. When comparing the data with those from current studies where mechanization prevails, it can be observed that the pain of work was not alleviated. It was concluded that suffering during this work activity is a present fact, mainly due to the gain being by production, and the biomechanical loads that cause great physical wear to this worker are intensified by the mental loads associated with this work.